Factors influencing purchase intention of Polytron Electric vehicles among Indonesian consumers - Muhammad Naufal Hilmi Al Farisi; Angga Pandu Wijaya (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study analyzes factors influencing the purchase intention of Polytron electric Vehicles in Indonesia by integrating the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB), with infrastructure barriers as an external factor. A quantitative approach surveyed purposively selected respondents, analyzing data through PLS-SEM using SmartPLS. The results indicate that perceived usefulness and perceived ease of use positively and significantly affect consumer attitudes. Consequently, attitude strongly drives purchase intention, effectively mediating the TAM constructs. Interestingly, infrastructure barriers show no significant direct impact on purchase intention, suggesting that short-distance mobility and battery rental models effectively mitigate consumer anxieties. This research guides the local automotive industry to prioritize operational convenience and budget efficiency to accelerate EV adoption and support decarbonization targets. Keywords: Technology Acceptance Model; Theory of Planned Behavior; Local Brand; Infrastructure Barriers; Consumer Attitude; Purchase Intention; Electric Vehicles